Compliance of infant formula promotion on websites of Brazilian manufacturers and drugstores - Isabella Scatamacchia Cordeiro Ferraz Prado; Ana Elisa Madalena Rinaldi (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To verify the compliance with Law No. 11,265/2006 in the promotion strategies for infant formula in Brazilian websites of manufacturers and drugstore networks. METHODS This was a cross-sectional study conducted in 2017. We analyzed the compliance to attributes of the Law No.11,265/2006 (Law for Marketing of Foods for Infants and Toddlers, Feeding Bottles, Teats and Pacifiers) in five websites of infant formula manufacturers and nine websites of drugstore networks. The main attributes assessed were: the presence of drawings or representations of children, the presence of warning statements displayed in conspicuous and prominent spaces informing if products are intended for infants aged under or over 6 months, the adequate display of infant formulas/similar products, and the presence of pop-ups with other infant formulas or links to websites for children's products. All compliances and non compliances verified were described in absolute and relative frequencies. RESULTS We verified that 80% of the websites of infant formula manufacturers displayed advertisements for other children's food products. The main non compliance in infant formula manufacturer's websites was the absence of warning statements about products intended for infants over 6 months of age. Only 33% of the drugstores' websites complied with Law No. 11,265/2006. The main non compliances in these websites were the absence of warning statements on products intended for infants over 6 months of age (100%), the presence of pop-up advertisements for other infant foods (77%) and the presence of advertisements for other children's food products (92%). CONCLUSION We identified non compliances with the Law No. 11,256/2006 in almost all websites of infant formula manufacturers and in all the websites of drugstore networks. Most promotion strategies were found at drugstore websites, which are the main channels for online sales.